2010
DOI: 10.1016/j.brat.2010.03.015
|View full text |Cite
|
Sign up to set email alerts
|

An 8-year follow-up of treated obese children: Children’s, process and parental predictors of successful outcome

Abstract: Objective This study presents an 8-year outcome of overweight children who were treated in an outpatient program and aims to identify child and familial variables associated with longterm weight regulation. Methods A total of 90 children participated with a mean age of 10.1 years ± 2.6 at baseline and a mean adjusted BMI (actual BMI/50 th percentile of BMI for age and gender x 100) of 153.1 ± 20.7% at baseline participated in the 8-year follow-up (retrieval rate 71%; response rate 89%). Children's and parental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 34 publications
2
71
1
6
Order By: Relevance
“…In a recent study by Moens et al, 18 it was found that age of the child, baseline BMI and self-worth were significant predictors of treatment success 8 years after follow up. In the current study, it was hypothesized that a younger age of the child, 19 the absence of parental overweight, 15,20 higher BMI percentile of the child before treatment, 19 higher socioeconomic status (SES), 21 higher motivation and greater parental attendance would positively influence treatment outcome.…”
Section: Introductionmentioning
confidence: 92%
“…In a recent study by Moens et al, 18 it was found that age of the child, baseline BMI and self-worth were significant predictors of treatment success 8 years after follow up. In the current study, it was hypothesized that a younger age of the child, 19 the absence of parental overweight, 15,20 higher BMI percentile of the child before treatment, 19 higher socioeconomic status (SES), 21 higher motivation and greater parental attendance would positively influence treatment outcome.…”
Section: Introductionmentioning
confidence: 92%
“…The degree of overweight has been shown to affect outcomes, with numerous studies having shown that higher initial body weight is associated with improved outcomes (Braet, 2006;Epstein, Valoski, Wing, & McCurley, 1994;Goossens, Braet, Van Vlierberghe, & Mels, 2009;Moens, Braet, & Van Winckel, 2010). One study also showed that increased overweight is related to poorer weight loss outcomes (Nowicka et al, 2008).…”
Section: Treatment Of Overweight and Obesitymentioning
confidence: 99%
“…Other predictors of improved outcomes include early treatment response (Goldschmidt et al, 2012;Jelalian et al, 2008), greater social support (Braet, 2006;Epstein et al, 1994;Moens et al, 2010), lower parental psychopathology (Epstein et al, 1994;Frohlich, Pott, Albayrak, Hebebrand, & Pauli-Pott, 2011;E. Moens et al, 2010), higher session attendance (Jelalian et al, 2010), and self-monitoring (Epstein, Valoski, Wing, & McCurley, 1990;Jelalian et al, 2010).…”
Section: Treatment Of Overweight and Obesitymentioning
confidence: 99%
“…Data from Rhee et al [36] suggested that parents having an older child, believing that they themselves were overweight, perceiving that their child had a health problem were associated with greater parental readiness to make changes. Emerging research also indicates that overweight children with psychosocial problems or the occurrence of maternal psychopathology are less responsive to weightcontrol intervention over the longer term [5,37]. There have been significant lifestyle changes in the family during the previous decades.…”
Section: Discussionmentioning
confidence: 99%